GRAMMATICAL TRANSFORMATIONS IN UZBEK AND ENGLISH LANGUAGES - Narzullayeva , Firuza Olimovna (Innovative Development in Educational Activities, 2023)
This article deals with the interlinguistic lexical and grammatical transformations, and types of transformation in Uzbek and English languages.